Pengaruh Shortage Cargo terhadap Kegiatan Transhipment Batu Bara di PT. Kartika Samudra Adijaya Site Berau - Faizal Akbar; Faris Novandi; Ardhiana Puspitacandri (Universitas 45 Surabaya, 2024)
One of the most common obstacles is the difference in the amount of coal transported during the transhipment process compared to before the transhipment was carried out. This difference tends to lead to a reduction in the amount of coal (shortage cargo) which is certainly very detrimental to the recipient company which causes the transhipment process to occur more than once, thus disrupting the company's schedule and operations, resulting in the parties involved experiencing financial losses. This study was conducted to determine the influence of draught survey factors, hydrostatic table and cargo losses and how the influence of each factor simultaneously causes cargo shortages in transhipment activities, testing using comparative causal quantitative research methods using multiple linear regression data analysis techniques which were then processed using the SPSS version 23 program. The results obtained indicate that there is an influence of draught survey, hydrostatic table and cargo losses on transhipment activities and partially have an influence of 9%, 1.6% and 2.5% respectively. The variables of draught survey, hydrostatic table and cargo losses simultaneously cause cargo shortages so that it affects transhipment by 71.2%. while the remaining 28.8% is suspected to be influenced by other factors outside the research variables.